Modern approaches to technical mastery formation among wrestlers of throw type by the example of Greco-Roman wrestling - Vasilev, G. F.; Tiunova, O. V.; Filchenkov, D. A. (Advances in Economics, Business and Management Research, 2020)
The article is about modern tendencies in scientific-methodical support development in training athletes-combatants. Main attention is paid to technical-tactical planning and the training process development. There appears the necessity to use a system approach in training athletes-combatants, competitive statistics thorough analysis and new evaluation criteria for the training process creation. The article presents distorting factors systematization in competitive activity. Methodical peculiarities of training throw type wrestlers are considered. The whole range of methodical theses of this article can be used in other kinds of sports single combats. Modern approaches analysis to technical mastery formation among throw type wrestlers by the example of Greco-Roman wrestling is the reason to reconsider methodical complex analysis of modern training system aspects among athletes-combatants. The article has not only methodical, but also survey character. It has the references to the main scientific-methodical articles of the authors according to this topic.